The Existence of Coffee Barista Education in Kota Lumpia (Semarang) - Prehanto, Adi; Haryono, Haryono; Raharjo, Tri Joko (Universitas Negeri Semarang, 2019)
Semarang is one of the big cities in Indonesia that owns many popularities, such as culture and education. Semarang as the capital city of Central Java, experiencing some developments in sectors. Instead, the coffee industry also developed in Semarang. This was appeared by a lot of cafes of coffee spread on every side of Semarang. The aimed of this research was to analyze the existence of barista education in Semarang indeed. The research method applied is a qualitative method. Through applying the method, would be found comprehensive results about the existence of education of coffee barista in Semarang. The technic of collecting data was done by interview, and deeply barista coffee education in Semarang existed because of the development and need for a competent barista for the coffee industry. This research implied to reinforce the theory of education, especially for barista coffee education.